Subcellular localization of MC4R with ADCY3 at neuronal primary cilia underlies a common pathway for genetic predisposition to obesity. (February 2018) - Siljee, Jacqueline; Wang, Yi; Bernard, Adelaide; Ersoy, Baran; Zhang, Sumei; Marley, Aaron; Von Zastrow, Mark; Reiter, Jeremy; Vaisse, Christian
Abstract Most monogenic cases of obesity in humans have been linked to mutations in genes encoding members of the leptin–melanocortin pathway. Specifically, mutations inMC4R, the melanocortin-4 receptor gene, account for 3–5% of all severe obesity cases in humans1–3 . Recently, ADCY3 (adenylyl cyclase 3) gene mutations have been implicated in obesity4, 5 . ADCY3 localizes to the primary cilia of neurons6, organelles that function as hubs for select signaling pathways. Mutations that disrupt the functions of primary cilia cause ciliopathies, rare recessive pleiotropic diseases in which obesity is a cardinal manifestation7 . We demonstrate that MC4R colocalizes with ADCY3 at the primary cilia of a subset of hypothalamic neurons, that obesity-associatedMC4R mutations impair ciliary localization and that inhibition of adenylyl cyclase signaling at the primary cilia of these neurons increases body weight. These data suggest that impaired signaling from the primary cilia of MC4R neurons is a common pathway underlying genetic causes of obesity in humans. MC4R colocalizes with ADCY3 at primary cilia in hypothalamic neurons, andMC4R mutations associated with human obesity impair this localization. Inhibition of adenylyl cyclase signaling at primary cilia of neurons leads to increased body weight in mice.